(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
William Blake was a visionary poet and artist who lived during the Romantic period. He is most known for his works that explore subject matter such as mysticism, spirituality, and the human soul. The purpose of this study is to investigate Blake’s unique representation of the divine and human existence by analysing the ways in which he related the physical and spiritual worlds via the use of symbolism, metaphysical imagery, and spiritual themes. Blake’s works, such as Songs of Innocence and Experience and The Marriage of Heaven and Hell, which call into question the conventional religious orthodoxy and instead embrace a more individualised and subjective notion of God, give a complex vision of the divine. Blake’s writings also challenge the traditional religious orthodoxy. We find a conflict between naiveté and experience in Blake’s poetry, as well as metaphorical descriptions of the soul and God. Blake’s poetry is the source of these ideas. The objective of this dissertation is to investigate the ways in which Blake used mysticism to criticise various cultural, political, and religious institutions while simultaneously expressing his spiritual beliefs. It does this by conducting an in-depth analysis of his mystically inspired vision. The study presented here makes use of Blake’s theological interpretations to demonstrate how the poet adopted a radical position in his investigation of spirituality, the human condition, and the age-old fight between good and evil.